PENGARUH MODEL DISCOVERY LEARNING TERHADAP KETERAMPILAN MENULIS TEKS LAPORAN HASIL OBSERVASI SISWA KELAS VII SMP NEGERI 15 PADANG - Syahrin Maulida; Syahrul R., (Jurnal Pendidikan Bahasa dan Sastra Indonesia, 2020)
ABSTRACT The purpose of this study is three, namely, first, describing the writing skills of the report text of the observation of class VII students of SMP Negeri 15 Padang before using based on discovery learning models. Second, describe the writing skills of the report report observation text of grade VII students at SMP Negeri 15 Padang after using based on discovery learning models. Third, describing the effect of based on discovery learning models on the writing skills of the report's observation text in grade VII students at SMP Negeri 15 Padang. There are two data of this study, namely the score of the results of the test writing skills in the report text of the seventh grade students of SMP Negeri 15 before and after using the based on the discovery learning model. Based on the results of the study, it was concluded three things, namely first, the writing skills of the report report observation text of class VII Padang 15 Public Middle School before using the based on discovery learning models in the Enough qualifications (C) with an average value of 61,46. Second, the report writing skills of the observation results of the seventh grade students of SMP Negeri 15 Padang after using the based on the discovery learning model are more than adequate (LdC) with an average value of 71.76. Third, there is a significant effect in the use of based on discovery learning models on the report writing skills of the observation results of class VII students at SMP Negeri 15 Padang because of the tcount> t table (4.17> 1.70).Kata kunci: Pengaruh, Model Discovery Learning, Laporan Hasil Observasi